Geographic region: Does it matter in cutaneous melanoma of the head and neck?. (5th June 2017) - Kılıç, Suat; Unsal, Aykut A.; Chung, Sei Y.; Samarrai, Ruwaa; Kılıç, Sarah S.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: The head and neck are two of the most common locations for cutaneous melanoma. We present the first population‐based analysis of geographic differences in anatomic subsite, clinicopathologic and demographical traits, histopathologic subtype, treatment modality, and disease‐specific survival (DSS) of cutaneous head and neck melanoma (CHNM). Study Design: Retrospective database analysis. Methods: The Surveillance, Epidemiology, and End Results database was queried for cases of CHNM reported between 2000 and 2013. Patients were grouped into East, Midwest, South, and West regions of the United States. Overall incidence, demographic traits, primary tumor site, clinicopathologic traits, histopathologic subtype, treatment modality, and DSS were compared among regions. Results: There were 49, 365 patients with CHNM identified. The West (4.60) and the South (4.42) had significantly higher incidence (per 100, 000) than the East (3.84) and Midwest (3.65) ( P < .05). DSS was significantly different among regions ( P < .0066). The East (5 years: 89.4%, 10 years: 84.1%) had the highest DSS rate, and the South (5 years: 87.0%, 10 years: 81.8%) had the lowest DSS rate. The Midwest (5 years: 88.4%, 10 years: 84.3%) and West (5 years: 88.3%, 10 years: 83.5%) had intermediate DSS. On multivariate analysis, the South had an elevated hazard ratio (1.17, 95% confidence interval: 1.05‐1.30) when compared to the West. Conclusions: Geographic region may play a significant role in CHNM. Incidence is higher in the South and the West. Incidence, histologic subtype, treatment modality, and DSS vary among regions. DSS is lower in the South than the West, even after accounting for other major prognostic factors. Level of Evidence: 4. Laryngoscope, 127:2763–2769, 2017